2019
DOI: 10.1002/adbi.201900164
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy Based on Circulating Cancer‐Associated Cells: Bridging the Gap from an Emerging Concept to a Mainstream Tool in Precision Medicine

Abstract: The concept of liquid biopsy and the isolation and analysis of circulating biomarkers from blood samples is proposed as a surrogate to solid biopsies and can have the potential to revolutionize the management of patients with cancer. The relevance of circulating tumor cells (CTCs) and the importance of the information they carry is acknowledged by the medical community. But what are the barriers to clinical adoption? This review draws a panorama of the biological implications of CTCs, their physical and bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 192 publications
(193 reference statements)
0
4
0
Order By: Relevance
“…cfDNA is short, fragmented DNA released from apoptotic or necrotic cancer cells able to provide information on cancer cells genetic and epigenetic mutations (Chen et al, 2020). However, due to its short half-life in the circulation, cfDNA applicability is limited, moreover, its sequencing needs highly sensitive assays such as next-generation sequencing (NGS) (Jimenez-Zenteno and Cerf, 2020). The development of novel techniques for the analysis of low-abundance DNA has allowed to exploit the potential of circulating tumor DNA (ctDNA) as a marker of cancer disease burden, predictor of therapy response or resistance (Cescon et al, 2020).…”
Section: Liquid Biopsymentioning
confidence: 99%
“…cfDNA is short, fragmented DNA released from apoptotic or necrotic cancer cells able to provide information on cancer cells genetic and epigenetic mutations (Chen et al, 2020). However, due to its short half-life in the circulation, cfDNA applicability is limited, moreover, its sequencing needs highly sensitive assays such as next-generation sequencing (NGS) (Jimenez-Zenteno and Cerf, 2020). The development of novel techniques for the analysis of low-abundance DNA has allowed to exploit the potential of circulating tumor DNA (ctDNA) as a marker of cancer disease burden, predictor of therapy response or resistance (Cescon et al, 2020).…”
Section: Liquid Biopsymentioning
confidence: 99%
“…Although this allows for the relative measurement of actin depletion and E of these cells, respectively, for comparison with each other, it may not give a true indication of what these values are in suspension. Indeed, it has previously been shown that the rigidity of cancer cells in suspension may increase to improve their chances of survival in the high-shear regimes that pervade the circulatory system (78)(79)(80). For this reason, future studies might use techniques that examine cell E in circulation such as optical tweezers or Tjunction deformation.…”
Section: Cell Elastic Modulusmentioning
confidence: 99%
“…Unlike standard invasive biopsies, ctDNA sequencing uses a small sample of the patient’s blood. As such it offers a promising non-invasive tool to evaluate tumour heterogeneity permitting multiple sampling and monitoring of treatment response [ 17 ]. Processes such as apoptosis, tissue necrosis, and possibly active secretion by cancerous and normal cells are thought to release nucleic acids (short-double stranded DNA fragments) into circulation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%